Description of hot debriefings after in-hospital cardiac arrests in an international pediatric quality improvement collaborative. (July 2018) - Sweberg, Todd; Sen, Anita I.; Mullan, Paul C.; Cheng, Adam; Knight, Lynda; del Castillo, Jimena; Ikeyama, Takanari; Seshadri, Roopa; Hazinski, Mary Fran; Raymond, Tia; Niles, Dana E.; Nadkarni, Vinay; et al.
Abstract: Background: The American Heart Association recommends debriefing after attempted resuscitation from in-hospital cardiac arrest (IHCA) to improve resuscitation quality and outcomes. This is the first published study detailing the utilization, process and content of hot debriefings after pediatric IHCA. Methods: Using prospective data from the Pediatric Resuscitation Quality Collaborative (pediRES-Q), we analyzed data from 227 arrests occurring between February 1, 2016, and August 31, 2017. Hot debriefings, defined as occurring within minutes to hours of IHCA, were evaluated using a modified Team Emergency Assessment Measure framework for qualitative content analysis of debriefing comments. Results: Hot debriefings were performed following 108 of 227 IHCAs (47%). The median interval to debriefing was 130 min (Interquartile range [IQR] 45, 270). Median debriefing duration was 15 min (IQR 10, 20). Physicians facilitated 95% of debriefings, with a median of 9 participants (IQR 7, 11). After multivariate analysis, accounting for hospital site, debriefing frequency was not associated with patient age, gender, race, illness category or unit type. The most frequent positive (plus) comments involved cooperation/coordination (60%), communication (47%) and clinical standards (41%). The most frequent negative (delta) comments involved equipment (46%), cooperation/coordination (45%), and clinical standards (36%). Conclusion: Approximately half of pediatric IHCAs were followed by hot debriefings. Hot debriefings were multi-disciplinary, timely, and often addressed issues of team cooperation/coordination, communication, clinical standards, and equipment. Additional studies are warranted to identify barriers to hot debriefings and to evaluate the impact of these debriefings on patient outcomes.